2017
DOI: 10.1093/arclin/acx019
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Estimation in Non-demented Parkinson's Disease

Abstract: Background: The Cognitive Estimation Test (CET) is widely used in clinical and research settings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…As the total score of NADL is obtained by the combination of all tasks included in the battery, overall worse performance may be related both to failure in the written operations task but also to slightly worse performance in all other tasks (see Table S2). Although these findings are consistent with previous evidence [11], the observed differences may be also related to the presence of cognitive impairments in our PD sample. In fact, PD patients obtained lower performances in MMSE compared to HC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As the total score of NADL is obtained by the combination of all tasks included in the battery, overall worse performance may be related both to failure in the written operations task but also to slightly worse performance in all other tasks (see Table S2). Although these findings are consistent with previous evidence [11], the observed differences may be also related to the presence of cognitive impairments in our PD sample. In fact, PD patients obtained lower performances in MMSE compared to HC.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, longer duration of the disease and more impaired global cognition were reported to be associated with a higher rate of arithmetic deficits, which were also predicted by impairments in the attention and visuospatial/constructional domains [10]. Moreover, Scarpina and collaborators [11] found that PD patients had an impaired performance on the Graded Difficulty Arithmetic task, which correlated with the outcome of numerical estimation tasks.…”
Section: Introductionmentioning
confidence: 96%
“…Even though one might expect arithmetic deficits to have been assessed thoroughly given the extensive profiling of cognitive impairment in PD, research is scarce (e.g., Kalbe, 1999;Tamura et al, 2003). Unsystematic clinical observations show arithmetic errors in both advanced PDD (Kalbe, 1999) and non-demented PD patients (Tamura et al, 2003;Zamarian et al, 2006;Scarpina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the task was self-paced; it would be interesting to perform the tasks in different (self-paced vs external-paced) modalities, but it should be taken into account that the overall accuracy and stability of movements can be negatively influenced by attentional processing enhanced by the presence of external cueing in PD (Almeida et al., 2005). Finally, the possible effect related to lateralization of symptoms, meaning which body part side was the most affected by disease, in relation to the dominance handedness, as well as the role of cognitive difficulties in PD (Litvan et al., 2011) and specifically in cognitive estimation (D’Aniello et al., 2015a,b; Scarpina et al., 2017) should be considered. Future research needs to overcome these limitations, where possible.…”
Section: Discussionmentioning
confidence: 99%